Complement profile in neonates of different gestational ages - Grumach, Anete; Ceccon, M. E.; Rutz, Renate; Fertig, Anja; Kirschfink, Michael (Scandinavian journal of immunology, 2014)
Blood levels of regulators of the complement system in preterm babies were reported in few studies only. The aim of this study was to set up a complement profile in premature and term babies focusing on the development of blood levels of MBL, key regulatory proteins and on classical pathway activity, which may allow an estimation of potential susceptibility to infection.
Gesehen am 18.09.2020